Poverty and Government Priorities for Action: Lessons from the Theory of Disruptive Innovations in Africa (Global Journal of Management and Business Research, 2019)
It is a fundamental mistake for the government in Africa to focus on modernizing infrastructure to address the issue of poverty among the population This had been the strategic mistake for the programme of the Government of the Democratic Republic of Congo s 5 chantiers which did not improve the social situation of the population The real question is how can innovations bring prosperity to a nation This article provides an answer to this question Based on an exploration of the existing literature in particular the new approach on disruptive innovations Clayton Christensen 2002 Clayton Christensen Efossa E et al 2019 this research aims to provide a new lens on priority choices that a government in Africa can take on the issue of poverty
Keywords: disruptive innovation; incremental inn ovation; poverty; strategic choice; prosperity; management; Africa